Date | May 2014 | Marks available | 12 | Reference code | 14M.1.hl.TZ0.14 |
Level | HL only | Paper | 1 | Time zone | TZ0 |
Command term | Determine, Hence, and Show that | Question number | 14 | Adapted from | N/A |
Question
(a) The function \(g\) is defined by \(g(x,{\text{ }}y) = {x^2} + {y^2} + dx + ey + f\) and the circle \({C_1}\) has equation \(g(x, y) = 0\).
(i) Show that the centre of \({C_1}\) has coordinates \(\left( { - \frac{d}{2}, - \frac{e}{2}} \right)\) and the radius of \({C_1}\) is \(\sqrt {\frac{{{d^2}}}{4} + \frac{{{e^2}}}{4} - f} \).
(ii) The point \({\text{P}}(a, b)\) lies outside \({C_1}\). Show that the length of the tangents from \({\text{P}}\) to \({C_1}\) is equal to \(\sqrt {g(a,{\text{ }}b)} \).
(b) The circle \({C_2}\) has equation \({x^2} + {y^2} - 6x - 2y + 6 = 0\).
The line \(y = mx\) meets \({C_2}\) at the points \({\text{R}}\) and \({\text{S}}\).
(i) Determine the quadratic equation whose roots are the x-coordinates of \({\text{R}}\) and \({\text{S}}\).
(ii) Hence, given that \(L\) denotes the length of the tangents from the origin \({\text{O}}\) to \({C_2}\), show that \({\text{OR}} \times {\text{OS}} = {L^2}\).
Markscheme
(a) (i) completing the square,
\({\left( {x + \frac{d}{2}} \right)^2} + {\left( {y + \frac{e}{2}} \right)^2} - \frac{{{d^2}}}{4} - \frac{{{e^2}}}{4} + f = 0\) M1A1
whence the centre \({\text{C}}\) is the point \(\left( { - \frac{d}{2}, - \frac{e}{2}} \right)\) and the radius is
\(\sqrt {\frac{{{d^2}}}{4} + \frac{{{e^2}}}{4} - f} \) AG
(ii) \({\text{C}}{{\text{P}}^2} = {\left( {a + \frac{d}{2}} \right)^2} + {\left( {b + \frac{e}{2}} \right)^2}\) (A1)
let \({\text{Q}}\) denote the point of contact of one of the tangents from \({\text{P}}\) to the circle.
\({\text{C}}{{\text{Q}}^2} = \frac{{{d^2}}}{4} + \frac{{{e^2}}}{4} - f\) (A1)
using Pythagoras’ Theorem in triangle \({\text{CPQ}}\), M1
\({L^2} = {\left( {a + \frac{d}{2}} \right)^2} + {\left( {b + \frac{e}{2}} \right)^2} - \left( {\frac{{{d^2}}}{4} + \frac{{{e^2}}}{4} - f} \right)\)
\( = {a^2} + {b^2} + da + eb + f = g(a, b)\) A1
therefore \(L = \sqrt {g(a,{\text{ }}b)} \) AG
[6 marks]
(b) (i) the x-coordinates of \({\text{R, S}}\) satisfy
\({x^2} + {(mx)^2} - 6x - 2mx + 6 = 0\) M1
\((1 + {m^2}){x^2} - (6 + 2m)x + 6 = 0\) A1
(ii) \({L^2} = g(0,{\text{ }}0) = 6\) A1
let \({x_1},{x_2}\) denote the two roots. Then \({x_1}{x_2} = \frac{6}{{1 + {m^2}}}\) A1
\({\text{OR}} = \sqrt {x_1^2 + {{(m{x_1})}^2}} = {x_1}\sqrt {1 + {m^2}} \) and \({\text{OS}} = {x_2}\sqrt {1 + {m^2}} \) M1
therefore
\({\text{OR}} \times {\text{OS}} = {x_1}{x_2}(1 + {m^2}) = 6\) A1
so that \({\text{OR}} \times {\text{OS}} = {L^2}\) AG
[6 marks]